Pengaruh Kompetensi Pegawai dan Komitmen Organisasi Terhadap Kualitas Laporan Keuangan Satuan Kerja Perangkat Daerah (SKPD) Di Kota Bandung - Nugraha, Nugraha; Triantoro, Arvian; Kurnia, Ika Famela (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2014)
The purpose of this study was to determine the effect of employee competence to quality financial statements, the effect of organizational commitment to quality financial reporting and jointly determine the effect of employee competency and organizational commitment to quality financial reporting unit (SKPD) in Bandung. The method used is the multiple correlations, analysis of a total of 39 units of work units on education entities. Respondents of this study are part of the staff at each entity and the financial inspectorate Bandung. Based on the analysis that had been done, that there is a positive effect between employee competencies against the quality of financial reporting by 41.8%. There is effect between organizational commitments to quality financial reporting by 37.6% and together the competence of employees and organizational commitment affect the quality of financial reporting unit (SKPD) in Bandung by 25.9% and its residual influenced by other factors.